Prevalence and incidence of Coats disease in a large claims database - Nobuhisa Ochiai; Kenji Fujimoto; Kazuma Oku; Hiroyuki Kondo (PLoS ONE, 2025)
Purpose To determine the prevalence and incidence of Coats disease in the Japan Medical Data Center (JMDC) claims database. Methods Data on patients with Coats disease were collected from the JMDC claims database that were collected over a five-year period between 2019–2023. The patients with were grouped by their sex and age. The prevalence and incidence were then calculated relative to all of the members in the JMDC database. The treatment rate was calculated as the ratio of patients receiving retinal photocoagulation or vitrectomy to the total number of patients over the five-year period. Results The age-adjusted prevalence of Coats disease in the JMDC database was 1.7/100,000 with 2.4 males to 0.9 females for the five-year period. The age-adjusted prevalence in children <20-years-of-age with Coats disease was 3.6/100,000 with 5.7 boys to 1.5 girls, while that of adults age ≥ 20 years was 1.3/100,000 with 1.7 males to 0.7 females. The age-adjusted incidence of Coats disease was 0.7/100,000 individuals with 1.0 males to 0.4 females, and for different ages, the age-adjusted incidence was 1.4/100,000 children (2.1 boys to 0.6 girls), and 0.6/100,000 adults (0.8 men to 0.3 women). The treatment rate was 21.9% for all Coats individuals with children having a significantly higher treatment rate of 28.0% than adults of 18.2%. Conclusion This is the first study that determined the prevalence and incidence of Coats disease in the JMDC database. The prevalence and incidence in children were approximately double that of adults. The proportion of females was higher among adults than among children.